Umami sea: flavoring innovation from fish waste in Gresik district to create sustainable blue economy - Hesti Rahmawati; Reza Astika Wahyu Pramesti; Nada Fariska Danisswari (PT. Gyandharma Global Media, 2025)
Gresik Regency, recognized for its rich fishery resources, is experiencing growing difficulties associated with unmanaged fish waste, which has detrimental effects on both the environment and community health. The